1995
DOI: 10.1111/j.1365-2265.1995.tb02642.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal consequences of maternal hypothyroidism in early pregnancy and inadequate replacement

Abstract: SummaryMaternal hypothyroidism may be associated with a variety of pregnancy compiicatlons. OBJECTIVE We have evaluated the perinatai consequences of maternal hypothyroidism in early and late gestation. DESIGN Retrospective study of pregnant women, wlth quasl-experlmentai design comparlng dlfferent subJects. SUBJECTS Forty-three pregnancies in 42 women with hypothyroidism -either biochemically hypothyroid or with a history of hypothyroidism on adequate replacement -and no other preexisting medical conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(42 citation statements)
references
References 25 publications
1
36
1
4
Order By: Relevance
“…Women with hypothyroidism have decreased fertility (9), even if they conceive, the risk of miscarriage is increased (19). The risk of gestational hypertension, pre-eclampsia and eclampsia, abruption placentae, post partum haemorrhage, premature delivery and IUGR is increased (20, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Women with hypothyroidism have decreased fertility (9), even if they conceive, the risk of miscarriage is increased (19). The risk of gestational hypertension, pre-eclampsia and eclampsia, abruption placentae, post partum haemorrhage, premature delivery and IUGR is increased (20, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that maternal hypothyroidism is associated with increased risks of abortions, stillbirths, preterm delivery, and pregnancy-induced hypertension [36]. Autoimmune thyroid disease is common in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism has adverse effects on the course of pregnancy and development of the fetus [2]. Several studies have reported that maternal hypothyroidism is associated with increased risks of abortions, stillbirths, preterm delivery, and pregnancy-induced hypertension [36]. Conversely, other reports have shown successful pregnancy outcomes in women who were profoundly hypothyroid [1].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Sahu et al (2010) reported a relatively high prevalence of 44–52% cesarean sections in a small group of patients with hypothyroidism, compared to 36% in the control group (Sahu et al, 2010). Wasserstrum & Anania (1995) reviewed 43 pregnancies of women with hypothyroidism and reported an increased rate of cesarean section due to fetal distress in women with ‘severe hypothyroidism’ (Wasserstrum & Anania, 1995). A previous study based on our population database, found a cesarean sections rate of 30% in pregnancies complicated by hypothyroidism (Cohen et al, 2011).…”
Section: Discussionmentioning
confidence: 99%